2018
DOI: 10.1002/lary.27061
|View full text |Cite
|
Sign up to set email alerts
|

Perception and duration of pain after office‐based vocal fold injection augmentation

Abstract: 4. Laryngoscope, 128:929-934, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…Similarly, Taliercio et al 20 reported that 76% described sore throat persisting for 3 postoperative days; 36% reported sore throat persisting beyond POD 3. Crawley et al 14 showed a similar phenomenon in their study of postprocedural pain after in-office vocal fold injection. A significant number of patients had pain a week after the procedure, also measured by the SF-MPQ.…”
Section: Discussionmentioning
confidence: 69%
“…Similarly, Taliercio et al 20 reported that 76% described sore throat persisting for 3 postoperative days; 36% reported sore throat persisting beyond POD 3. Crawley et al 14 showed a similar phenomenon in their study of postprocedural pain after in-office vocal fold injection. A significant number of patients had pain a week after the procedure, also measured by the SF-MPQ.…”
Section: Discussionmentioning
confidence: 69%
“…Of the included studies, 9 were prospective randomized trials, 15-23 4 were prospective nonrandomized cohort studies, 24-27 47 were prospective case series, 28-74 22 were retrospective reviews, 75…”
Section: Resultsmentioning
confidence: 99%
“…30,36,53,58,84 The Wong-Baker FACES scale was used in 2 studies 46,87 and the McGill Pain Questionnaire in 2 as well. 38,63 The Iowa Satisfaction with Anesthesia Scale was used by a single study. 66 Patient tolerance—as assessed via a patient’s ability to complete the entirety of a procedure—was the primary pain assessment method in 22 studies † and was reported as a secondary assessment of postprocedural pain in 2 additional studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study tracked patient pain levels during and following in-office procedures and suggested that stretched tissues may cause increased or longer durations of pain. 20 The ability to harness the findings of this study to produce streamlined injection procedures may reduce procedural time and stretching or damage to surrounding tissue from efforts to maintain needle stability during injection laryngoplasty. These results may also translate to other procedures that use these materials.…”
Section: Discussionmentioning
confidence: 98%